2001
DOI: 10.1128/iai.69.11.6660-6669.2001
|View full text |Cite
|
Sign up to set email alerts
|

toxB Gene on pO157 of Enterohemorrhagic Escherichia coli O157:H7 Is Required for Full Epithelial Cell Adherence Phenotype

Abstract: Adherence of enterohemorrhagic Escherichia coli (EHEC) to the intestinal epithelium is critical for initiation of a bacterial infection. An in vitro infection study previously indicated that EHEC bacteria initially adhere diffusely and then proliferate to develop MC, a process that is mediated by various secreted proteins, such as EspA, EspB, EspD, Tir, and intimin, as well as other putative adherence factors. In the present study, we investigated the role of a large 93-kb plasmid (pO157) in the adherence of O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
164
0
3

Year Published

2003
2003
2016
2016

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 186 publications
(172 citation statements)
references
References 43 publications
3
164
0
3
Order By: Relevance
“…ToxB is encoded on the pO157 plasmid in EHEC O157:H7 strains (41). This suggests that lifA/efa1/toxB and the LEE (and its T3SS) are closely associated and that LifA/Efa1/ToxB are probably core effectors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…ToxB is encoded on the pO157 plasmid in EHEC O157:H7 strains (41). This suggests that lifA/efa1/toxB and the LEE (and its T3SS) are closely associated and that LifA/Efa1/ToxB are probably core effectors.…”
Section: Discussionmentioning
confidence: 99%
“…Their proposed functions in different A/E pathogens range from being a lymphotoxin and immune modulator (37,55), an adhesion/colonization factor (38,40,41), and a regulator of type III secretion (40,41,56), to being a modulator of Rho GTPases and intestinal epithelial-barrier function (52). These observations suggest that LifA/Efa1/ToxB have host cell binding activities and likely exert some of their functions from the bacterial side.…”
Section: Discussionmentioning
confidence: 99%
“…• Otros factores de virulencia de ECST: Adicionalmente, el plásmido pO157 de ECST codifica genes para catalasa-peroxidasa (katP) 56 , adhesina ToxB 57 , metaloproteasa dependiente de zinc (StcE) 58-61 y para la enterohemolisina (Ehx) 59 , cuyas funciones están principalmente enfocadas a mediar la unión a la célula hospedera, degradación de mucinas y glicoproteínas, regular mecanismos de inflamación y citotoxicidad, entre otras [56][57][58][59][60][61][62][63] .…”
Section: Artículo Originalunclassified
“…The reasons why efa-1/lifA mutations affect expression and secretion of type III secreted proteins in some EHEC strains but not others require further investigation. It is possible that functional redundancy may exist, whereby loss of Efa-1/LifA in some strains may be compensated for by other proteins that are similarly able to modulate type III secretion, such as ToxB (Tatsuno et al, 2001). Indeed, we observed that EHEC O26 strain 193 harbours toxB, whereas EHEC O111 strain E45035N and EHEC O5 strain S102-9 did not contain the gene as assessed by PCR with toxB-specific primers (Tozzoli et al, 2005; data not shown).…”
Section: Discussionmentioning
confidence: 65%
“…EHEC O157 : H7 strains also contain a homologue of Efa-1/LifA on their large plasmid (ToxB). ToxB promotes adherence of EHEC O157 : H7 to cultured cells and, as with efa-1/lifA in EHEC O5 : H-and O111 : H-, mutation of the gene impairs the expression and secretion of LEE4-encoded proteins at a post-transcriptional level (Tatsuno et al, 2001). However, ToxB was not required for intestinal colonization of calves and neither it, nor the truncated Efa-1, appears to confer lymphostatinlike activity (Abu-Median et al, 2006).…”
Section: Introductionmentioning
confidence: 99%